1986
DOI: 10.1111/j.1477-8947.1986.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy Use in Rural Areas: A Study of Ten Villages in India

Abstract: Fig. 1. Location of the ten villages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the study villages, century-old open or partly-closed chulhas, which have very low thermal efficiency, are used in almost all households. The innovations to increase end-use efficiency have not been able to make much headway due to economic, infrastructural, and sociocultural conditions and designing methods associated with these innovations (Geller 1982;Bowonder et al 1986;Agarwal 1986, pp. 77-105).…”
Section: Mil Qureshi and S Kumarmentioning
confidence: 99%
“…In the study villages, century-old open or partly-closed chulhas, which have very low thermal efficiency, are used in almost all households. The innovations to increase end-use efficiency have not been able to make much headway due to economic, infrastructural, and sociocultural conditions and designing methods associated with these innovations (Geller 1982;Bowonder et al 1986;Agarwal 1986, pp. 77-105).…”
Section: Mil Qureshi and S Kumarmentioning
confidence: 99%
“…Rural energy planners designing schemes to make village self-sufficient with regard to their energy needs are naturally interested in obtaining information relating to the existing energy consumption habits. Several studies have been reported in the literature that attempts to shed light on the energy consumption behaviour of rural areas in different Indian states [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. This information can be used to study and modify the proposed resource allocation policy to the satisfaction of the rural population.…”
Section: Introductionmentioning
confidence: 99%